Peran Gender dalam Ritual Penjamasan Pusaka - Kamal, Moh. Zainol; Effendi, Ahmad; Indriyani, Nufil; Wardi, Moh. (Proceedings of Annual Conference for Muslim Scholars, 2025)
This research examines the Penjamasan Pusaka tradition in Aeng Tong Tong, Sumenep, as a sacred ritual that transcends the preservation of heirlooms to serve as a medium for identity reinforcement, social legitimacy, and communal harmony. The study specifically analyzes the construction, negotiation, and transmission of gender roles within the ritual’s power dynamics. Utilizing an ethnographic approach, data were gathered through participant observation, documentation, and in-depth interviews with traditional leaders, village officials, and ritual committees. The findings reveal a complex gender structure: while men dominate the public domain—leading processions and maintaining authoritative legitimacy—women occupy strategic spiritual, symbolic, and logistical roles essential to the ritual's continuity. These relations reflect a complementary pattern that fosters social cohesion, yet simultaneously reveals power asymmetries rooted in local patriarchal culture. The study concludes that Penjamasan Pusaka serves as a vital arena for gender representation where local wisdom facilitates social harmony. This traditional model remains highly relevant to global discourses on cultural sustainability, equality, and the preservation of indigenous heritage in a modernizing world.